PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BEI PERIODE 2016-2018 - Varid Martah (BORJUIS: JURNAL OF ECONOMY, 2024)
The company's operations can have a negative impact on the environment and surrounding communities, so that social responsibility needs to be done to improve the image of businesses in the eyes of consumers. Social responsibility carried out by the company can make consumers more confident that business people not only seek profit but also have concern. The existence of CSR is also an activity that requires costs in its implementation which can have an impact on the financial position. The purpose of this study was to determine the effect of Corporate Social Responsibility Disclosure on financial performance. Profitability ratio is one of the ratios that can measure financial conditions using Return on Assets and Return on Equity. This research is an empirical study using purposive sampling for data collection procedures. The sample in this study were basic and chemical industry companies listed on the Indonesia Stock Exchange for the period of 2016-2018, as many as 22 out of 63 companies had met the qualifications. So that the number of research data analyzed was 66 data. This research was processed using a simple regression test method. The results of the study explained that partially (1) CSR had a significant negative effect on ROA, which means that the higher the CSR activities undertaken could reduce the rate of return on assets. (2) CSR has no significant negative effect on ROE, which means that high or low CSR activities undertaken cannot affect the rate of return on equity.